Management of Marfan Syndrome, with a Specific Focus on the Significance of Physical Activity in this Patient Population - Patrycja Jędrzejewska-Rzezak (Quality in Sport)
Introduction: Marfan syndrome is an autosomal dominant disorder of connective tissue. Timely diagnosis and effective therapy are essential for individuals with Marfan syndrome, as they are susceptible to severe cardiovascular consequences, including aortic aneurysms and aortic dissection. The conventional treatment comprises beta-blockers to mitigate the dilatation of the aorta and aortic surgery. The efficacy of contemporary medicinal and surgical interventions in Marfan syndrome has significantly enhanced mean life expectancy. International guidelines generally discourage physical activity for individuals with Marfan syndrome. Recent recommendations have created exclusions for these patients, indicating benefits from engaging in low-intensity physical activity exclusively.